Defense Styles, approaches to learning and the mediating role of academic procrastination - Vlachopanou, Patra; Karagiannopoulou, Evangelia (Pure and Applied Science Advances, 2023)
The present study belongs to the research that concerns the investigation of the relationship among academic procrastination, defense styles and approaches to learning. Specifically, it aims to explore the mediating role of academic procrastination in the relationship between defense styles and approaches to learning. The sample comprises 628 Greek university undergraduates (78% women and 22% men) who attend a four-year degree program. The questionnaires Defense Style Questionnaire-88, Procrastination Assessment Scale Questionnaire, Flourishing Scale, and HowULearn are used in the study. Results reveal the mediating role of academic procrastination in the relationship between maladaptive and adaptive defense style and approaches to learning. Academic procrastination seems to be a self-handicapping/defensive role between mental health variables and learning. Findings are discussed in the context of recent literature.